Quo Vadis Esensi Lembaga PKPU Pasca-Putusan Mahkamah Konstitusi Nomor 23/PUU-XIX/2021 - Antonius Sidik Maryono; Ulil Afwa; Sindy Riani Putri Nurhasanah (CV Rewang Rencang, 2022)
Recognition of the authority of creditors in filing applications for Suspension of Payment (PKPU) at the implementation level is often misused by creditors with bad intentions as a shortcut to bankrupt debtors. Therefore, the Constitutional Court through Ruling Number 23/PUU-XIX/2021 decided to open space for an appeal against PKPU whose reconciliation proposal was rejected by creditors. But on the other hand, the existence of decisions that are final, binding, and erga omnes a quo arises skepticism of the essence and principles contained in the payment suspension institution itself. Moving on from these problems, this study aimed to analyze the juridical implications of Ruling Number 23/PUU-XIX/2021 on the existence and essence of the PKPU institution in Indonesia. This type of research is doctrinal research that relies on secondary data. The findings in this study indicated that the opening of an appeal in PKPU due to the rejection of the peace proposal by creditors has the potential to cause uncertainty, and injustice to parties with good intentions, and distort the essence of the payment suspension institution itself. The basic problem that allowed distortion of the payment suspension institution is that the filing requirements were too simplistic, thus creating a high possibility for the bankruptcy of solvent debtors.